Smart Technology Trends in Industrial and Business Management - Cagáňová, Dagmar; Balog, Michal; Knapčíková, Lucia; Soviar, Jakub; Mezarcıöz, Serkan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents current developments in smart city research and application regarding the management of manufacturing systems, Industry 4.0, transportation, and business management. It suggests approaches to incorporating smart city innovations into manufacturing systems, with an eye towards competitiveness in a global environment. The same pro-innovative approach is then applied to business and cooperation management. The authors also present smart city transportation solutions including vehicle data processing/reporting system, mobile application for fleet managers, bus drivers, bus passengers and special applications for smart city buses like passenger counting system, IP cameras, GPS system etc. The goal of the book is to establish channels of communication and disseminate knowledge among researchers and professionals working on smart city research and application. Features contributions on a variety of topics relatedto smart cities from global researchers and professionals in a wide range of sectors; Presents topics relating to smart cities such as manufacturing, business, and transportation; Includes expanded selected papers from EAI International Conference on Management of Manufacturing Systems (MMS 2016), EAI Industry of Things and Future Technologies Conference - Mobility IoT 2016 and International Conference on Smart Electric Vehicles and Vehicular Ad-hoc NETworks (SEVNET).
Chapter1: Designing Behavioral Changes in Smart Cities using Interactive Smart Spaces -- Chapter2: Industry 4.0: Preparation of Slovak Companies, the Comparative Study -- Chapter3: Transformations of urbanized landscape following the Smart Water Management concept -- Chapter4: Social Innovations in Context of Smart City -- Chapter5: Application of AHP Method in Decision-making Process -- Chapter6: Towards Creating Place Attachment and Social Communities in the SMART Cities -- Chapter7: A New Approach to Sustainable Reporting: Responsible Communication between Company and Stakeholders in Conditions of Slovak Food Industry -- Chapter8: An integrative spatial perspective on energy transition - renewable energy niches -- Chapter9: Can concept of smart governance help to mitigate the climate in the cities? -- Chapter10: Potential of Human Resources as Key Factor of Success of Innovation in Organisations -- Chapter11: Environmental Policy as a Competitive Advantage in the Global Environment.-Chapter12: Awareness of Malicious Behavior as a Part of Smart Transportation in Taxi Services -- Chapter13: Alternative lights for public transport in Smart Cities -- Chapter14: Green Markets and Their Role in the Sustainable Marketing Management -- Chapter15: Introduction to the International Conference on Management of Manufacturing Systems (MMS 2016) -- Chapter16: Smart wristband system for improving quality of life for users in traffic environment -- Chapter17: Composites manufacturing: A new approaches to simulation -- Chapter18: Study of the cutting zone of the WPC composite materials after different types of cutting -- Chapter19: Quality assurance in the automotive industry and Industry 4.0 -- Chapter20: RFID labels and its characteristics on labeled products -- Chapter21: Risk analysis causing downtimes in production process of hot rolling mill -- Chapter22: Evaluation of roughness parameters of machined surface of selected wood plastic composite -- Chapter23: Basic assumptions of information system for increasing competitiveness of production company within EU and their application at the CAPP system design -- Chapter24: Operational characteristics of experimental actuator with a drive based on the antagonistic pneumatic artificial muscles -- Chapter25: IoT challenge: older test machines modernization in an automotive plant -- Chapter26: Critical values of some probability distributions and standard numerical methods -- Chapter27: Measuring production process complexity -- Chapter28: Evaluation of the transverse roughness of the outer and inner surfaces of the thin-walled components produced by milling -- Chapter29: Smart transportation applications and vehicle data processing system for smart city buses -- Chapter30: Current Trends in Industrial and Business Management in Smart Technology -- Chapter31: Sustainable Organization of Cooperation Activities in a Company - Slovak republic research perspective -- Chapter32: Cooperation as a key element between Universities and Factories -- Chapter33: Zilina Intelligent Manufacturing System - best practice of cooperation between university and research center -- Chapter34: Cooperative relations and activities in a cluster in the Slovak and Czech automotive industry -- Chapter35: Model Approach for Formation Synergy Effects in Automotive Industry with Support of Big Data Solutions - application for distribution and transport service strategy -- Chapter36: Improvement of the production system based on the Kanban principle.
Keywords: Telecommunication; Signal processing; Manufactures; Production management; Industrial Management; Business information services; Communications Engineering, Networks; Signal, Speech and Image Processing; Machines, Tools, Processes; Production; Industrial Management; IT in Business